2000
DOI: 10.1097/00002030-200003310-00008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of tuberculosis transmission in prisons: an analysis using conventional and molecular methods

Abstract: In the prison system studied, the recent transmission of TB contributes substantially to the overall incidence of the disease. Both lengthy incarcerations and delays in identifying inmates with pulmonary symptoms play a key role in this recent transmission. Directly observed therapy (DOT) is a critical control strategy for reducing the emergence of drug resistance and for avoiding the transmission of resistant organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1
7

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 43 publications
1
23
1
7
Order By: Relevance
“…During the last 15 years, ME has been broadly used in the study of TB transmission, representing an important improvement in the detection and description of TB clusters, (6,20,21,22,30,34) as well as in studies of TB transmission at a population level (2,5,11,12,19). Since the beginning of its use, several studies have shown a proportion of cases with no correlation between the results of the two methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 15 years, ME has been broadly used in the study of TB transmission, representing an important improvement in the detection and description of TB clusters, (6,20,21,22,30,34) as well as in studies of TB transmission at a population level (2,5,11,12,19). Since the beginning of its use, several studies have shown a proportion of cases with no correlation between the results of the two methods.…”
Section: Discussionmentioning
confidence: 99%
“…Among the control measures currently in use, the detection of new infections and secondary cases by conventional contact tracing (CCT) is fundamental (39). During the last 15 years, molecular epidemiology (ME) techniques have been demonstrated to be helpful in the study of TB transmission, and they have been applied to population studies (2,5,11,12,19,30), such as those of defined risk groups (22,34) and analyses of outbreaks (6,20,21).…”
mentioning
confidence: 99%
“…Patients were grouped in the same cluster if their isolates were identical with respect to the number and size of hybridizing bands when six or more bands are present. 22 …”
Section: Epidemiological Characterizationmentioning
confidence: 99%
“…The prison population is predominantly young and male with a low education level and prisoners usually originate from disadvantaged communities with high TB rates (March et al 2000). The prisoners usually live in unhealthy settings and do not have the resources or habits to keep themselves healthy.…”
mentioning
confidence: 99%